'Confined Dreams' of Informal Skills Learners: Can TVET Widen Their Aspirations? (Journal of Technical and Vocational Education and Training, 2021)
More than eighty percent of youth in Nepal are estimated to be learning their livelihood-skills through work. Generally, those informal skills learners either never visit a school or discontinue their school education and start a career without formal or non-formal skills training. Adopting the qualitative research approach, and underpinned by career development theories, I argue that those people have to confine their aspirations due to unfavorable TVET system. I also use poetic inquiry to analyze and present the information. I also discuss how the country's TVET system can support such a massive number of informal skills learners. The research is based on in-depth interviews conducted with six youth and adults working in three different trades— pottery, fast-food, and motorcycle service mechanics located in Kathmandu Valley. It is concluded that the struggle at school and the path of work faced by those adolescents and youths for getting a job are diverse. It is also found that informal skills learners have aspirations, mainly limited to either establishing or extending the existing enterprise with their competence acquired through workplace learning. The paper concludes that the state should facilitate fulfilling the aspirations of those informal skills learners.